2021
DOI: 10.1590/0103-8478cr20201043
|View full text |Cite
|
Sign up to set email alerts
|

Nigeria’s cocoa exports: a gravity model approach

Abstract: What are the major factors affecting Nigeria’s cocoa export flows? In answering this question, the authors suggest a commodity-specific gravity model with three different analytical approaches, (the Heckman Sample Selection Model, the Generalised Least Square, and the Poisson Pseudo Maximum Likelihood), based on a period of 24 years of panel data for Nigeria and it’s 36 importing partners to estimate the models. The results showed that GDP, exchange rate policy, WTO, EU, and colonial link are positively associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…For instance, the agricultural sector provides vast employment for rural inhabitants, raw materials for agroindustries and contributes remarkably to non-oil revenue and export. As remarked by Abdullahi et al (2021), Nigeria is an agrarian country where agricultural activities are the primary source of economic survivals and livelihoods. Consequently, several administrations evolved series of policy interventions to enable the sector maintain its indispensable roles.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the agricultural sector provides vast employment for rural inhabitants, raw materials for agroindustries and contributes remarkably to non-oil revenue and export. As remarked by Abdullahi et al (2021), Nigeria is an agrarian country where agricultural activities are the primary source of economic survivals and livelihoods. Consequently, several administrations evolved series of policy interventions to enable the sector maintain its indispensable roles.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, many researchers have used the gravity model to investigate a commodityspecific model to determine the factors affecting a single commodity's exports. For instance, Abdullahi, Shahriar [35] studied the gravity equation for Nigeria's cocoa exports with its 36 major importing partners from 1995-2018. The study confirmed the consistence of the gravity model assumptions in the context of the Nigerian cocoa industry.…”
Section: Plos Onementioning
confidence: 99%
“…Prior international trade literature considered distance as a trade resistance factor and is anticipated to decrease China's agricultural trade [35,69]. The distance between Beijing and importing partners' capital city is taken as a proxy for trade costs.…”
Section: Factors Affecting China's Agricultural Products Exportmentioning
confidence: 99%
“…Around 85% of its residents are ethnic Somalis who have historically inhabited in the country's north. Ethnic minorities are largely concentrated in the south [6,7]. The official languages of Somalia are Somali and Arabic [6].…”
mentioning
confidence: 99%
“…miles). 46.8% of the population is urban (7,431,038 people in 2020). The median age in Somalia is 16.7 years.…”
mentioning
confidence: 99%